Advancements in Airway Management and Ventilation in a Prehospital Cardiac Arrest: A Narrative Review - Yazeed Abdullah Alghamdi, Hani Salah ObidAlsobh, Abdulrahman Ali Alsubhi, Nawaf Fraih Sulaiman Alshammari, Mohammed Khalid Mohammed Alzhrani, Saad Saleh Hadi Al Mansournur, Yahya Saleh Hadi Al Mansour, Saleh Mahdi Hamad Alshammari; Lafi Gaffal Saeah Alshammari, Abdullah Khaled Alasoy Alenazi‎‏, Hmad Muhdy Atiah Alonzi, Obeid Ali Abdoah Alshammri, Faisal Abdullah Rade Alanezi, Abdullah Nawar Mana Alotaibi, Abdulaziz Huidi Alotaby, Sharar Abdullah Lafi Alotaibi (Journal of International Crisis and Risk Communication Research, 2024)
Out-of-hospital cardiac arrest (OHCA) remains a leading cause of death worldwide, with survival rates heavily dependent on the quality of prehospital advanced life support (ALS). Among the critical components of ALS, optimal airway management and ventilation strategies are essential to ensuring adequate oxygenation and facilitating effective resuscitation. This narrative review examines the evolution and current best practices in airway management and ventilation during prehospital resuscitation for OHCA. A comprehensive overview of traditional and emerging techniques, including bag-valve mask (BVM) ventilation, supraglottic airway devices (SADs), and endotracheal intubation, is provided, with a particular focus on their respective advantages and limitations in prehospital settings. Additionally, the role of mechanical chest compression devices, ventilator use, and feedback mechanisms in improving the quality of resuscitation are explored. The review also addresses the critical role of training, experience, and team dynamics, emphasizing the importance of specialized care teams, including prehospital physicians and anesthesiologists, in optimizing outcomes. Despite ongoing challenges and variations in clinical practice, the evidence suggests that a systematic approach, informed by up-to-date guidelines, feedback, and continuous professional development, is vital for improving patient survival rates in OHCA. By integrating advanced airway management techniques with optimized ventilation strategies, prehospital care providers can significantly enhance the efficacy of resuscitation efforts, ultimately improving the chances of survival and neurological recovery for OHCA patients.